Beban Kerja Perawat Di Ruang Instalasi Gawat Darurat (IGD) RSUD H. Ishak Umarela - Hasna Tunny; Siti Rochmaedah (Lembaga Pengembangan Kinerja Dosen, 2023)
Nurses have many duties and responsibilities set by the hospital, so the work carried out by nurses can provide its own workload due to the many tasks and pressures that exist. This workload will ultimately cause pressure on nurses, thereby affecting the performance of nurses. This study aims to look at the workload of nurses in the emergency room at RSUD H. Ishak Umarela. The research design used in this research is descriptive observational research. This research is to describe the workload of nurses at RSUD H. Ishak Umarella., which will take place from June-July 2023, involving 14 nurses using a total sampling technique. The variables in this research are workload which is divided into heavy, medium and light workload. Data collection used a Time And Motion Study method questionnaire. The research results showed that the majority of nurses workload in the emergency room at H. Ishak Umarela Hospital was light (64.3%). The care provided is an average of 49.9%, where this figure is less than productive time, so it can be concluded that the workload of nurses in the emergency room at RSUD H. Ishak Umarela.